Heutagogical learning in professional development: A bibliometric analysis of published literature between 2010 and 2024 - Verma, Vaibhav (Journal of Interdisciplinary Studies in Education, 2025)
This study explores the evolution and significance of heutagogical learning in professional development using a bibliometric analysis of literature published between 2010 and 2024. Heutagogy, emphasizing learner autonomy and self-determined learning, has emerged as a transformative educational paradigm, particularly in the context of workforce training and lifelong learning. The research employs a bibliometric approach to analyze 473 peer-reviewed publications sourced from Scopus, highlighting trends, influential authors, collaborative networks, and key thematic areas. Findings indicate a notable rise in publications since 2016, driven by the increasing demand for adaptive and autonomous learning strategies. Prominent contributions come from multidisciplinary domains, including social sciences, medicine, and computer science, underscoring the broad applicability of heutagogical principles. Co-authorship and co-citation analyses using VOSviewer reveal robust global collaborations, with significant contributions from institutions in the US, UK, and Australia. Key thematic clusters, such as self-directed learning, digital education, and professional adaptability, were identified, reflecting the relevance of heutagogical practices in addressing 21st-century workforce challenges. In order to maximise heutagogy’s potential for cultivating flexible, adaptable individuals, this study promotes inclusive research approaches and real-world applications. The results offer significant perspectives for scholars, decision-makers, and professionals who seek to include heutagogical approaches into professional development initiatives.